Characterization of the first bovine gammaherpesvirus 4 strain isolated from an aborted bovine fetus in Argentina - Romeo, Florencia; Manrique, Julieta; Perez, Sandra; Louge Uriarte, Enrique Leopoldo; Marin, Maia Solange; Canton, German Jose; Leunda, Maria Rosa; González Altamiranda, Erika; Pereyra, Susana Beatriz; Spetter, Lucas Maximiliano; Odeon, Anselmo Carlos; Jones, Leandro; et al. (Springer Verlag, 2020)
Bovine herpesvirus 4 (BoHV-4) is increasingly believed to be responsible for several disorders of the bovine reproductive tract. The first characterization of BoHV-4 in Argentina was from samples from an aborted fetus. Argentinean isolates are highly diverse and are phylogenetically grouped in three genotypes. In this study, we describe the isolation of BoHV-4 from a bovine fetus with a gestational age of 8 months and without macroscopic lesions. Genetic analyses revealed that the isolated strain belongs to genotype 2. This is the first report on the presence of infectious BoHV-4 in tissues from an aborted bovine fetus